Repeatability of Aberrometry-Based Automated Subjective Refraction in Healthy and Keratoconus Subjects - Carracedo, Gonzalo (J Ophthalmol, 2020)
PURPOSE: To compare the intersession repeatability of the Eye Refract, a new instrument to perform aberrometry-based automated subjective refraction, on healthy and keratoconus subjects. MATERIALS AND METHODS: A cross-sectional and randomized study was performed. A total of 64 participants were evaluated in the study, selecting one eye per participant randomly. The sample was divided into two different groups: 33 healthy subjects (38.85 ± 13.21 years) and 31 with keratoconus (37.29 ± 11.37 years). Three refractions per participant with the Eye Refract were performed on three different days, without cycloplegia. The repeatability analysis of refractive variables (M, J0, and J45), binocular corrected distance visual acuity (BCDVA), and spent time in refraction was performed in terms of repeatability (S(r)), its 95% confidence interval (r), and intraclass correlation coefficient (ICC). RESULTS: There were no statistically significant differences (P ≥ 0.05) between sessions in both groups for all refractive variables (M, J0, and J45) and BCDVA. Spent time in refraction was reduced as the sessions went by (P < 0.05). The Eye Refract was more repeatable for refractive errors assessment in healthy subjects (M : S(r) = 0.27 D; J0 : S(r) = 0.09 D; J45 : S(r) = 0.06 D) compared to those with keratoconus (M : S(r) = 0.65 D; J0 : S(r) = 0.29 D; J45 : S(r) = 0.24 D), while it was similar for BCDVA. CONCLUSIONS: The Eye Refract offered better repeatability to assess refractive errors in healthy subjects compared to those with keratoconus. Despite measurements being also consistent in keratoconus subjects, they should be treated with caution in clinical practice.